VD_FINDINFO HC / 2024 / 182 vom 23. Dezember 2024 - VD Tribunal cantonal (2024)
DIVORCE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE, ADMISSION PARTIELLE, PRÉVOYANCE PROFESSIONNELLE | 124b al. 2 CC, 285 CC